Central pattern generator and human locomotion in the context of referent control of motor actions - Feldman, Anatol G.; Levin, Mindy F.; Garofolini, Alessandro; Piscitelli, Daniele; Zhang, Lei (Clinical neurophysiology, 2021)
•Human locomotion likely results from changes in neurophysiological parameters that shift stable body equilibrium in space.•Central pattern generator and descending systems set the threshold muscle lengths at which motoneurons and reflexes begin to act.•Proprioceptive feedback is vital for converting central influences on motoneurons into shifts of threshold muscle lengths. Unperturbed human locomotion presumably results from feedforward shifts in stable body equilibrium in the environment, thus avoiding falling and subsequent catching considered in alternative theories of locomotion. Such shifts are achieved by relocation of the referent body configuration at which multiple muscle recruitment begins. Rather than being directly specified by a central pattern generator, multiple muscles are activated depending on the extent to which the body is deflected from the referent, threshold body configuration, as confirmed in previous studies. Based on the referent control theory of action and perception, solutions to classical problems in motor control are offered, including the previously unresolved problem of the integration of central and reflex influences on motoneurons and the problem of how posture and movement are related. The speed of locomotion depends on the rate of shifts in the referent body configuration. The transition from walking to running results from increasing the rate of referent shifts. It is emphasised that there is a certain hierarchy between reciprocal and co-activation of agonist and antagonist muscles during locomotion and other motor actions, which is also essential for the understanding of how locomotor speed is regulated. The analysis opens a new avenue in neurophysiological approaches to human locomotion with clinical implications.